(untitled) (ModaPalavra e-periódico, 2020)
This paper propose a methodology for creating color ranges from the identification of the design steps. The proposal consists of establishing the color range as a synthesis of the relation of variables that guide the selection of colors by objective criteria. The methodology relies on the Baxter decision funnel diagram and outlines 3 specific steps: branding, trends and theme - moodboarding. The steps are contextualized in the phases of research and generation of ideas and detailed a ccording to the practice of creating color charts for the development of products.